Systematic Review of Value Engineering Research Studies In Indonesia - Miraj, Perdana; Dofir, Ahmad; Andreas, Azaria; Berawi, Mohammed Ali; Bari, Saipol (UI Scholars Hub, 2019)
Value engineering (VE) plays a significant role in improving project competitiveness and propose an alternative solution to create added value for a project. Despite well-adopted in various countries worldwide, VE development shows stagnant progress in Indonesia. This can be seen by number of project and publications involving VE in Indonesia. In fact, academics and researchers argued the concept will highly contribute to advocate the benefits of VE into the public and private project practice. The research aims to investigate publications affiliated with Indonesian institutions and recommend strategies for VE implementation in the country. This paper uses a systematic review by taking into account the database library for extraction. The result shows that academics and researcher from Indonesian institutions regularly publish their work in VE study. However, the number of publication in refereed journals is much less compared papers in proceedings. The findings suggest some strategies to increase the publication and how to be involved in project development in Indonesia.